THE INFLUENCE OF PRODUCT QUALITY, BRAND IMAGE AND PROMOTION ON THE DECISION TO PURCHASE TEA GLASS IN MALIKUSSALEH UNIVERSITY STUDENTS - Niswatun Munawarah; Halida Bahri; Naufal Bachri; Khairina (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to determine the effect of product quality,brand image and promotion on purchasing decisions for glass tea at Malikussaleh University students. Promotion on Purchasing Decisions for glass tea at Malikussaleh University students. This research was conducted on Malikussaleh University Faculty of Economics and Business students who had purchased glass tea. The data used in this study are primary data obtained by distributing questionnaires via google form to 96 respondents. The data analysis technique used is multiple linear regression analysis using SPSS software assistance. The results showed that product quality had no significant effect on purchasing decisions for glass tea, Brand Image had a negative and significant effect on purchasing decisions, and promotion had a significant effect on purchasing decisions.